Interdependent transcription of a natural sense/antisense transcripts pair (SLC34A1/PFN3) - Zinad, H; Sae-Lee, C; Ariza-Mateos, M; Adamson, G; Khazeem, M; Knox, A; Chung, G; Mann, J; Werner, A (MDPI, 2022)
Natural antisense transcripts (NATs) constitute a significant group of regulatory, long noncoding RNAs. They are prominently expressed in testis but are also detectable in other organs. NATs are transcribed at low levels and co-expressed with related protein coding sense transcripts. Nowadays NATs are generally considered as regulatory, long noncoding RNAs without closer focus on the inevitable interference between sense and antisense expression. This work describes a cellular system where sense and antisense transcription of a specific locus (SLC34A1/PFN3) is induced using epigenetic modifiers and CRISPR-Cas9. The renal cell lines HEK293 and HKC-8 do not express SLC34A1/PFN3 under normal culture conditions. Five-day exposure to dexamethasone significantly stimulates sense transcript (SLC34A1) levels and antisense (PFN3) minimally; the effect is only seen in HEK293 cells. Enhanced expression is paralleled by reduced sense promoter methylation and an increase in activating histone marks. Expression is further modulated by cassettes that stimulate the expression of sense or antisense transcript but disrupt protein coding potential. Constitutive expression of a 5′-truncated SLC34A1 transcript increases sense expression independent of dexamethasone induction but also stimulates antisense expression. Concordant expression is confirmed with the antisense knock-in that also enhances sense expression. The antisense effect acts on transcription in cis since transient transfection with sense or antisense constructs fails to stimulate the expression of the opposite transcript. These results suggest that bi-directional transcription of the SLC34A1/PFN3 locus has a stimulatory influence on the expression of the opposite transcript involving epigenetic changes of the promoters. In perspective of extensive, previous research into bi-directionally transcribed SLC34A loci, the findings underpin a hypothesis where NATs display different biological roles in soma and germ cells. Accordingly, we propose that in somatic cells, NATs act like lncRNAs–with the benefit of close proximity to a potential target gene. In germ cells, however, recent evidence suggests different biological roles for NATs that require RNA complementarity and double-stranded RNA formation.